Study of Antimicrobial Effects of Clarithromycin Loaded PLGA Nanoparticles against Clinical Strains of Helicobacter pylori - Lotfipour, F.; Valizadeh, H.; Milani, M.; Bahrami, N.; Ghotaslou, R. (Drug Research, 2016)
Clarithromycin (CLR) formulation was prepared as PLGA nanoparticles in order to enhance the therapeutic effects using the distinctive features of a nanoparticulate delivery system. CLR loaded PLGA nanoparticles were prepared by Quasi Emulsion Solvent Diffusion (QESD) method using Poly lactic-co-Glycolic Acid (PLGA) as a biodegradable polymer. Antibacterial activity of the prepared formulations was evaluated against clinical strains of Helicobacter pylori, isolated from gastric biopsies of patients with gastritis, duodenal ulcer, peptic ulcer, and gastroesophageal reflux disease undergoing endoscopy, by using agar dilution method.Spherical nanoparticles with relatively narrow size distribution (between 200 and 800 nm) in the size range of 305±138, 344±148 and 362±110 nm were achieved for F22, F23 and F23 respectively. CLR encapsulation percentages were measured to be 57.4±4.3 to 80.2±4.0%. CLR loaded PLGA nanoparticles showed equal or enhanced eradication effect against H. pylori strains according to the declined MIC values in comparison with the untreated CLR.In conclusion, the prepared CLR nanoformulation showed appropriate physicochemical properties and improved activity against H. pylori that could be a suitable candidate for oral preparations.
Keywords: clarithromycin; nanoparticles; helicobacter pylori; minimum inhibitory concentration